A study of 159 Portuguese patients with familial amyloidotic polyneuropathy (FAP) whose parents were both unaffected. Issue 4 (April 1994) - Coelho, T; Sousa, A; Lourenço, E; Ramalheira, J
Abstract : We reviewed 1233 cases of familial amyloidotic polyneuropathy (FAP) from 489 Portuguese families registered at the Centro de Estudos de Paramiloidose, Porto, Portugal. It was found that in 159 cases, neither parent had shown symptoms of this hereditary dominant form of peripheral neuropathy. These cases appear to form a distinct group, with a later age at onset (mean 45.1 years, SD 12.0) than the group of patients with one affected parent (mean 31.2 years, SD 6.9) and a geographical origin not quite in the areas where the disease is most prevalent. Though this group is not significantly different from the general group of patients in clinical presentation at onset and severity of the disease, the average interval between onset and diagnosis (mean 4.5 years, SD 3.2) reflects the difficulties in diagnosing these patients in the absence of a positive family history. From the analysis of pedigrees and in spite of a large number of isolated cases, the occurrence of new mutations could not be proven, and it seems more likely that, in some families, the FAP gene may result in a milder expression or even remain "silent" for several generations. Further investigation of this discrepancy may prove to be important in elucidating the mechanisms involved in the pathogenetic process.